2002
DOI: 10.1046/j.1365-2958.2002.02757.x
|View full text |Cite
|
Sign up to set email alerts
|

A cytoplasmic coiled‐coil domain is required for histidine kinase activity of the yeast osmosensor, SLN1

Abstract: Summary The yeast histidine kinase, Sln1p, is a plasma membrane‐associated osmosensor that regulates the activity of the osmotic stress MAP kinase pathway. Changes in the osmotic environment of the cell influence the autokinase activity of the cytoplasmic kinase domain of Sln1p. Neither the nature of the stimulus, the mechanism by which the osmotic signal is transduced nor the manner in which the kinase is regulated is currently clear. We have identified several mutations located in the linker region of the Sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 61 publications
6
53
0
Order By: Relevance
“…This region (between residue 147 and residue 168) is predicted to have a high propensity for coiled-coil structure, a structure commonly found in other histidine kinases (13). Because of the dynamic nature of the helices, these coiled-coil structures might be used as a structural relay by sensing the conformational changes in the sensor domain upon the binding of a ligand and communicating this signal to the kinase core (26). Mutations in the linker region of Sln1P increase the activity of this kinase (26), as do similar mutations in NarX (10).…”
Section: Discussionmentioning
confidence: 99%
“…This region (between residue 147 and residue 168) is predicted to have a high propensity for coiled-coil structure, a structure commonly found in other histidine kinases (13). Because of the dynamic nature of the helices, these coiled-coil structures might be used as a structural relay by sensing the conformational changes in the sensor domain upon the binding of a ligand and communicating this signal to the kinase core (26). Mutations in the linker region of Sln1P increase the activity of this kinase (26), as do similar mutations in NarX (10).…”
Section: Discussionmentioning
confidence: 99%
“…The F220D mutation in helix II of either the EnvZ, Tez1, or Tez1A1 linker causes an OmpC c phenotype in all cases, implying that mutations at helix II of the linker alter the helical orientation of the predicted coiled-coil structure so that the enzymatic functions of the downstream catalytic domain of EnvZ can no longer be modulated by external signals. It has been shown that signal transduction in several receptor proteins is regulated by altering the coiled-coil orientation (20,35).…”
Section: Discussionmentioning
confidence: 99%
“…This domain is often found in proteins involved in the signaling system of prokaryotes, and the proteins are called HAMP (Histidine kinase, Adenyl cyclase, Methyl accepting chemotaxis protein, Phosphatase). Studies have shown that the HAMP domain is important in relation to the role of the sensor kinase, and is involved in intermolecular interactions (Pollard et al, 2009;Swain & Falke, 2007;Tao et al, 2002). In N. crassa, B. cinerea and C. heterostrophus, the deletions of the HAMP domain or amino acid-substituted mutations resulted in hyper-osmosensitivity and fungicide resistance, clearly indicating that this domain is essential for the function of Group III HisK (Cui et al, 2002;Ochiai et al, 2001;Yoshimi et al, 2004).…”
Section: Group-iii Hisk and Its Role In Filamentous Fungimentioning
confidence: 99%